Generating Chinese Ci with Designated Metrical Structure - Zhang, Richong; Liu, Xinyu; Chen, Xinwei; Hu, Zhiyuan; Xu, Zhaoqing; Mao, Yongyi (Proceedings of the AAAI Conference on Artificial Intelligence, 2019)
Ci is a lyric poetry form that follows highly restrictive metrical structures. This makes it challenging for a computer to compose Ci subject to a specified metrical requirement. In this work, we adapt the CVAE framework to automated Ci generation under metrical constraints. Specifically, we present the first neural model that explicitly encodes the designated metrical structure for Ci generation. The proposed model is shown experimentally to generate Ci with nearly perfect metrical structures.